Emotional Coping Strategies for Informal Caregivers of Hospitalized Patients: A Study of Distress and Overload - Oleas Rodríguez, Daniel Alfonso; Yong Peña, Christian; Garza Olivares, Xochitl; Teixeira Filho, Fernando Silva [UNESP]; Lucero Córdova, Jonathan Enrique; Salas Naranjo, Andy Jesús (Taylor & Francis, 2024)
Purpose: Informal caregivers constitute a vulnerable population group that has forsaken their activities and life projects with the sole purpose of caring for a dependent individual without receiving any form of compensation in return. Emotionally, this population has been neglected by both the state and family members, exacerbating distress levels among them. The objective is to analyze the impact of emotional coping strategies on the experiences of distress and emotional burden among adult informal caregivers tending to hospitalized individuals. Sample and Methods: The role of emotional coping strategies in caregiver burden and psychological distress was examined in 460 informal adult caregivers from Guayaquil, Ecuador, who participated in an online survey. The instruments used included the Depression, Anxiety, and Stress Scale (DASS 21), the Zarit Burden Inventory (ZBI), and the Emotional Coping Questionnaire (Cuestionario de Afrontamiento Emocional). The analysis involved a multiple regression to iteratively select variables, aiming to build a simpler and more explanatory model. Results: Employing multiple regression analysis with a stepwise model selection procedure, it was found that 16.5% of the variance in depression, 19.5% of the variance in anxiety, 19.8% of the variance in stress, and 32% of the variance in burden were predicted by specific coping strategies. Additionally, the impact of burden was estimated by the participants’ gender, with greater burden observed among males due to societal role expectations. Conclusion: This study underscores the importance of emotional coping in the experience of informal caregivers and suggests that psychological interventions should focus on developing adaptive strategies to manage the stress and emotional burden associated with caregiving.
Keywords: anxiety; cognitive emotion regulation; depression; emotion regulation; emotional overload; stress